Reproducibility and flexibility of monoclonal antibody production with Nicotiana benthamiana. Issue 1 (31st December 2022) - Swope, Kelsi; Morton, Josh; Pogue, Gregory P.; Burden, Leigh; Partain, Nicholas; Hume, Steve; Shepherd, John; Simpson, Carrie A.; Brennan, Miles B.; Furman, Thomas C.; Kingrey-Gebe, Sheila; Martinez, Theresa; et al.
ABSTRACT: The ongoing SARS-CoV-2 coronavirus pandemic of 2020–2021 underscores the need for manufacturing platforms that can rapidly produce monoclonal antibody (mAb) therapies. As reported here, a platform based on Nicotiana benthamiana produced mAb therapeutics with high batch-to-batch reproducibility and flexibility, enabling production of 19 different mAbs of sufficient purity and safety for clinical application(s). With a single manufacturing run, impurities were effectively removed for a representative mAb product (the ZMapp component c4G7). Our results show for the first time the reproducibility of the platform for production of multiple batches of clinical-grade mAb, manufactured under current Good Manufacturing Practices, from Nicotiana benthamiana . The flexibility of the system was confirmed by the results of release testing of 19 different mAbs generated with the platform. The process from plant infection to product can be completed within 10 days. Therefore, with a constant supply of plants, response to the outbreak of an infectious disease could be initiated within a matter of weeks. Thus, these data demonstrated that this platform represents a reproducible, flexible system for rapid production of mAb therapeutics to support clinical development.